PELATIHAN PENGARUHNYA TERHADAP KOMPETENSI SDM PADA DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN BANDUNG BARAT - Cynthia Lestiary; Yunus Suryana (Holistik Manajemen: Jurnal Manajemen, 2021)
The purpose of this study is to determine the effect of the Training on Human Resources Competency in the Department of Tourism and Culture of West Bandung Regency partially and simultaneously. This study used a descriptive and quantitative analysis methods. Collecting data in this study using census techniques, where all employees Office of Tourism and Culture of West Bandung Regency totaling 60 employees, used as subjects in this study. The technique of collecting data using questionnaires. Techniques using Path analysis and partial hypothesis testing and simultaneous with the t test and F test of linear regression equations were conducted, the results show that the Training have an influence on Human Resources Competency. Based on the results of the t test partial and F test (simultaneous) showed that the Training has a significant and positive effect on Human Resources Competency. This explains that if the Training is improved it will be able to improve HR Competency at the Department of Tourism and Culture of West Bandung Regency.